CONSORT item adherence in top ranked anaesthesiology journals in 2011. Issue 2 (February 2015) - Münter, Nils H.; Stevanovic, Ana; Rossaint, Rolf; Stoppe, Christian; Sanders, Robert D.; Coburn, Mark
<x xml:space="preserve">Abstract</x> BACKGROUND Randomised controlled trials (RCTs) are the gold standard for measuring the efficacy of any medical intervention. The present study assesses the implementation of the CONSORT statement in the top 11 anaesthesiology journals in 2011. OBJECTIVES We designed this study in order to determine how well authors in the top 11 ranked anaesthesiology journals follow the CONSORT statement's criteria. DESIGN A retrospective cross-sectional data analysis. SETTING The study was performed at the RWTH Aachen University Hospital. PARTICIPANTS Journals included Pain, Anesthesiology, British Journal of Anaesthesia, Regional Anesthesia and Pain Medicine, European Journal of Pain, Anesthesia and Analgesia, Anaesthesia, Minerva Anestesiologica, Canadian Journal of Anesthesia, Journal of Neurosurgical Anesthesiology and the European Journal of Anaesthesiology. MAIN OUTCOME MEASURES All articles in the online table of contents from the top 11 anaesthesiology journals according to the ISI Web of Knowledge were screened for RCTs published in 2011. The RCTs were assessed using the CONSORT checklist. We also analysed the correlation between the number of citations and the adherence to CONSORT items. RESULTS We evaluated 319 RCTs and found that, more than ten years after the publication of the CONSORT statement, the RCTs satisfied a median of 60.0% of the CONSORT criteria. Only 72.1% of the articles presented clearly defined primary and secondary outcome parameters. The number of citations is only weakly associated with the fulfilment of the CONSORT statement (r2 = 0.023). CONCLUSION Adherence to the CONSORT criteria remains low in top-ranked anaesthesiology journals. We found only a very weak correlation between the number of citations and fulfilment of the requirements of the CONSORT statement.